CONCEPTUAL METAPHOR OF ‘HEART’ IN POPULAR JAVANESE LOVE SONG - M. Suryadi; Vina Uctuvia (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
Metaphor is the use of language that is effective and expressive which causes metaphors to be found in the use of creative language, especially songs or poetry. Metaphors are now used in popular songs, especially in dangdut koplo songs. This research is supported by conceptual metaphor theory and image schema theory. The objective of this study is to explore any metaphors in the concept of 'heart' in song lyrics and how the concept of 'heart' is conceptualized in these collections of popular koplo songs. This study uses descriptive qualitative research design that consistent with the aims of this research. Data obtained by means of documentation. The data used is a collection of popular Javanese songs sung by Denny Caknan. In collecting data using documentation techniques. The data that has been collected is then analyzed using the direct element distribution and selection technique, which is realized by selecting song lyrics that contain the heart lexicon. Furthermore, the results of data analysis will be presented with an informal method. Based on the results of the analysis, there are two types of metaphors from the category of conceptual metaphors, namely ontological metaphors and structural metaphors. Two types of metaphors were also found from the image schema category, namely containment image schema and force image schema. From the analysis, it can be concluded that in Denny Caknan’s song represent some of conceptualization of the ati ‘heart’ metaphor, those are; (1) 'THE HEART IS HUMAN', (2) ‘HEART IS A CONTAINER CAN BE FILLED’, and (3) ‘THE HEART IS AN ENTITY CAN HANG OR GRASP’.